Effects of different orthodontic appliances on Actinomyces spp. (Asian Journal of Medical and Biological Research, 2024)
This study aims to identify the presence of Actinomyces species in the oral flora during orthodontic treatments using removable appliances and fixed wire technique, and to track changes throughout the treatment process. In this study, subgingival and supragingival plaque samples obtained from 48 patients undergoing orthodontic treatment at a dental facilities of Ataturk University, Türkiye were utilized as the primary material. The study groups comprised individuals undergoing fixed orthodontic treatment, those using removable appliances, and individuals who had not undergone any orthodontic treatment. Plaque samples were collected from the patients at the initiation of treatment and six months thereafter. After selective culturing in a specific medium, dental plaque samples were purified and subjected to microbial analysis using the VITEK 2 system (Biomerieux). The study aimed to identify and compare the microbial content of plaque samples from different orthodontic treatment groups. Actinomyces species were identified in all groups at both the initiation of treatment (T0) and six months later (T1) periods. At the beginning of treatment, Actinomyces species were found in 33 samples, while at six months, they were present in 18 samples. The curent study revealed similar microorganisms among the groups at both T0 and T1 periods. The Actinomyces species identified in this study include Actinomyces meyeri, Actinomyces naeslundii, and Actinomyces odontolyticus. It is evident that orthodontic treatments significantly impact oral health and that Actinomyces microorganisms are always likely to be present in the oral flora.Asian J. Med. Biol. Res. 2024, 10(1), 1-8